2015
DOI: 10.7717/peerj.1317
|View full text |Cite
|
Sign up to set email alerts
|

Assessing shoreline exposure and oyster habitat suitability maximizes potential success for sustainable shoreline protection using restored oyster reefs

Abstract: Oyster reefs provide valuable ecosystem services that contribute to coastal resilience. Unfortunately, many reefs have been degraded or removed completely, and there are increased efforts to restore oysters in many coastal areas. In particular, much attention has recently been given to the restoration of shellfish reefs along eroding shorelines to reduce erosion. Such fringing reef approaches, however, often lack empirical data to identify locations where reefs are most effective in reducing marsh erosion, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…; La Peyre et al . ). Using data from multiple projects over an extended timeframe, La Peyre et al .…”
Section: Regulating Servicesmentioning
confidence: 97%
See 3 more Smart Citations
“…; La Peyre et al . ). Using data from multiple projects over an extended timeframe, La Peyre et al .…”
Section: Regulating Servicesmentioning
confidence: 97%
“…Many waterways suffer from the introduction of heavy shore defences due to the concentrated load upon soft sediments: the results of which can require additional efforts and funds in order to help maintain the breakwater structures (Piazza et al 2005). Oyster reefs, however, act as biological barriers to reduce erosion, and do not require additional upkeep once established (Scyphers et al 2011;La Peyre et al 2015). Using data from multiple projects over an extended timeframe, La Peyre et al (2015) found that oyster reefs reduced marsh retreat by an average of 1 m yr À1 along moderately exposed and highly exposed shores.…”
Section: Carbon Sequestration (Regulation Of Biophysical Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the objectives of ecological research on oyster reef living shorelines should focus on the factors that affect the persistence of oysters on the reef structure ( predict the locations for successful oyster growth and oyster reef living shorelines (e.g. Fuchs & Reidenbach, 2013;La Peyre et al, 2015).…”
Section: Application Of Ecological Principlesmentioning
confidence: 99%